A New Approach to Spirulina Cultivation - Vardapetyan, H. E.; Movsesyan, R. A.; Nalbandyan, G. G. (ՀԱԱՀ հիմնադրամ)
This paper presents an overview of a novel approach to spirulina microalgae cultivation. The most optimal design of a photobioreactor with compact dimensions and, at the same time, a large production area is proposed. The research areas that can significantly impact increasing spirulina cultivation productivity are outlined. Results of studies confirm the relatively high productivity of spirulina cultivation, which is more than 30 g/l of dry biomass per 1 sq. m per a day.
Keywords: Agricultural Engineering